Association of suicidal ideation with demographic, lifestyle and health factors in Malaysians - Yong, Kang Cheah; Omar, Mohd Azahadi; Siew, Nooi Phang; Abd. Manaf, Noor Hazilah (Hong Kong Academy of Medicine Press, 2018)
Objective: To determine the association of suicidal ideation with demographic, lifestyle, and health factors, using data from National Health and Morbidity Survey 2011 (NHMS 2011) of Malaysia.